Three-month vs. one-year detraining effects after multicomponent exercise program in hypertensive older women - Leitão, Luis (2022)
Background: Chronic diseases are the leading causes of death and disability in older women. Physical exercise training programs promote beneficial effects for health and quality of life. However, exercise interruption periods may be detrimental for the hemodynamic and lipidic profiles of hypertensive older women with dyslipidemia. Methods: Nineteen hypertensive older women with dyslipidemia (exercise group: 67.5 ± 5.4 years, 1.53 ± 3.42 m, 71.84 ± 7.45 kg) performed a supervised multicomponent exercise training program (METP) during nine months, followed by a one-year detraining period (DT), while fourteen hypertensive older women (control group: 66.4 ± 5.2 years, 1.56 ± 3.10 m, 69.38 ± 5.24 kg) with dyslipidemia kept their continued daily routine without exercise. For both groups, hemodynamic and lipidic profiles and functional capacities (FCs) were assessed four times: before and after the METP and after 3 and 12 months of DT (no exercise was carried out). Results: The METP improved hemodynamic and lipidic profiles (p < 0.05), while three months of DT decreased all (p < 0.05) parameters, with the exception of diastolic blood pressure (DBP). One year of DT significantly (p < 0.01) decreased systolic blood pressure (7.85%), DBP (2.29%), resting heart rate (7.95%), blood glucose (19.14%), total cholesterol (10.27%), triglycerides (6.92%) and FC—agility (4.24%), lower- (−12.75%) and upper-body strength (−12.17%), cardiorespiratory capacity (−4.81%) and lower- (−16.16%) and upper-body flexibility (−11.11%). Conclusion: Nine months of the exercise program significantly improved the hemodynamic and lipid profiles as well as the functional capacities of hypertensive older women with dyslipidemia. Although a detraining period is detrimental to these benefits, it seems that the first three months are more prominent in these alterations.